Copper-catalyzed N-methylation/ethylation of sulfoximines. Issue 39 (2nd September 2015) - Teng, Fan; Cheng, Jiang; Yu, Jin-Tao
Abstract : A protocol for the copper-catalyzed N -methylation/ethylation of sulfoximines using peroxide as a methyl/ethyl source was developed. Abstract : A protocol for the copper-catalyzed N -methylation of sulfoximines with di- tert -butyl peroxide (DTBP) was developed. This protocol has good functional group tolerance leading to N -methylated sulfoximines in moderate to good yields. Besides, N -ethylation of sulfoximines was achieved in the presence of bis(1, 1-dimethylpropyl)peroxide as the ethylating agent under a standard procedure.